Risk Factors for Progressive Chronic Kidney Disease in Children with Idiopathic Nephrotic Syndrome at Dr. Mohammad Hoesin General Hospital Palembang - Maulana, Mirza Gifari; Eka Intan Fitriana; Phey Liana; Hertanti Indah Lestari; Dalilah (HM Publisher, 2023)
Nephrotic syndrome (NS) is a kidney disease that is often found in children. NS can cause infectious and non-infectious complications, such as upper respiratory tract infections, urinary tract infections, edema, acute kidney injury (AKI), and hypertension. This study aimed to determine the risk factors of age, gender, nutritional status, hypertension, hematuria, AKI, hyperfiltration, and steroid sensitivity to the progression of chronic kidney disease (CKD) in children with the initial idiopathic NS in the pediatric ward of Dr. Mohammad Hoesin General Hospital Palembang. This study was an analytic observational study with a cross-sectional design. A total of 72 secondary data of research subjects were included in this study. Risk factor analysis was carried out with the help of SPSS version 24 software in univariate, bivariate, and multivariate ways. The most common risk factor for children with the initial idiopathic NS is age ≥10 years, males and females gender obtained the same number, and the nutritional status of obesity, hematuria, AKI, and hyperfiltration have quite low rates. However, hypertension and SRNS have high rates in children with initial idiopathic NS. In conclusion, hypertension and hyperfiltration are risk factors that play a role in initiating the progression of idiopathic NS to CKD in the pediatric ward of Dr. Mohammad Hoesin General Hospital, Palembang.